PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM PERUSAHAAN JASA TRANSPORTASI - Siska Septina; Fifi Swandari (Universitas Lambung Mangkurat, 2018)
This research as “Effect Fundamental Factors toward stock return of Transportation’s Company”. Aims analyzed fundamental factors to haven influence stock return of transportation company at Indonesia Stock Exchange (BEI). Fundamental factors such as Earning Per Share (EPS), Book Value Per Share (BVS), Price Earning Ratio (PER), Debt to Equity Ratio (DER), Return on Asset (ROA), and Return On Equity (ROE). Methodology research used purposed sampling with criteria as 1. Stock of Transportation company which listed fm th. 2009-2013. 2.Stocked was trade at Indonesian Stock Exchange (BEI). Sample totally 13 and data analysis with multiple regression of ordinary least square and hypothesis test used F statistics and t statistic at level significance 5%. Analysis result is fm totally 6 (six) of fundamental factors, only Price Earning Ratio (PER), Debt to Equity Ratio (DER) and Return on Asset (ROA) significance influance stock return of 13 (thirteen) transportation company at BEI, while others are not significance. The future result suggested to expand other fundamental factors and suggested to add more variabels so can get better result